Balancing biodiversity outcomes and pollution management in urban stormwater treatment wetlands. (1st March 2019) - Hale, Robin; Swearer, Stephen E.; Sievers, Michael; Coleman, Rhys
Abstract: Wetlands are increasingly being constructed to mitigate the effects of urban stormwater, such as altered hydrological regimes and reduced water quality, on downstream aquatic ecosystems. While the primary purpose of these wetlands is to manage stormwater, they also attract animals whose growth, survival and breeding (i.e. 'fitness') may be compromised. Such deleterious effects will be exacerbated if animals are caught in 'ecological traps', mistakenly preferring wetlands with unsuitable environmental conditions. Alternatively, wetlands that offer suitable habitat conditions for animals could be beneficial, especially in fragmented urban landscapes. Consequently, a thorough understanding of the potential ecological impacts of stormwater treatment wetlands is critical for managing unintended consequences to urban biodiversity. To help facilitate this understanding, we draw upon findings from a four-year research program conducted in the city of Melbourne in south-eastern Australia as a case study. First, we summarise our research demonstrating that some stormwater wetlands can be ecological traps for native frogs and fish in the study region, whilst others likely provide important habitat in areas where few natural waterbodies remain. We use our work to highlight that while stormwater wetlands can be ecological traps, their effects can be properly managed. We propose the need for a better understanding of the ecological consequences of changes to wetland quality and their population-level impacts across the landscape. We hope that this study will generate discussions about how to most effectively manage constructed wetlands in urban landscapes and more research for a better understanding of the issues and opportunities regarding potential ecological traps. Highlights: Urban stormwater wetlands can have both ecological benefits and costs. Some urban stormwater wetlands are ecological traps. Better understanding the ecological consequences of changes to wetlands is vital.